2013
DOI: 10.4081/gh.2013.53
|View full text |Cite
|
Sign up to set email alerts
|

Climatic factors associated with amyotrophic lateral sclerosis: a spatial analysis from Taiwan

Abstract: Abstract. Few studies have assessed the spatial association of amyotrophic lateral sclerosis (ALS) incidence in the world. The aim of this study was to identify the association of climatic factors and ALS incidence in Taiwan. A total of 1,434 subjects with the primary diagnosis of ALS between years 1997 and 2008 were identified in the national health insurance research database. The diagnosis was also verified by the national health insurance programme, which had issued and providing them with "serious disabli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…No significant correlation has been found for AD/D or ALS/MND patients. On the other hand, a lower increment in ALS/MND prevalence was found in the HT as compared to the LT clusters indicating that, for these patients, a higher temperature could somehow protect from the disease, as confirmed by the positive effect of observed sunlight exposure on reduced disease incidence in the Taiwan population, regardless of environmental warming [ 14 ]. Anyway, the higher climate temperature and/or a progressive environmental warming are reported to lead directly or indirectly to the enhancement of oxidative stress, changes in cerebrovascular hemodynamics, excitotoxicity, and microglial activation, which are all factors implicated in ALS/MND pathogenesis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant correlation has been found for AD/D or ALS/MND patients. On the other hand, a lower increment in ALS/MND prevalence was found in the HT as compared to the LT clusters indicating that, for these patients, a higher temperature could somehow protect from the disease, as confirmed by the positive effect of observed sunlight exposure on reduced disease incidence in the Taiwan population, regardless of environmental warming [ 14 ]. Anyway, the higher climate temperature and/or a progressive environmental warming are reported to lead directly or indirectly to the enhancement of oxidative stress, changes in cerebrovascular hemodynamics, excitotoxicity, and microglial activation, which are all factors implicated in ALS/MND pathogenesis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study found NO (nitrogen oxide), NO 2 , and Cd (cadmium) to be positively correlated with ALS and O 3 to be inversely correlated, while benzopyrene was not found to be correlated [128]. The other study found positive correlations between ALS and both precipitation and sun exposure [129].…”
Section: Qualitative Synthesismentioning
confidence: 95%
“…For example, an approach for PD in Thailand (population 67 million) using 3 independent administrative sources achieved only 66% case ascertainment. 20 Registers from Scandinavia, 21 Canada, 22 the United States, 23 and Taiwan 24 have ascertained cases using administrative EHRs. As exemplified by a prescription-based register for AD in Finland requiring stringent proof of diagnosis, such an approach can successfully exclude coding errors if administrative records are a priori designed to ensure reliability in ascertainment.…”
Section: Existing Population-based Registers Inmentioning
confidence: 99%